Adaptation Aftereffects in the Perception of Crabs and Lobsters as Examples of Complex Natural Objects - Reindl, Antónia; Schubert, Torsten; Strobach, Tilo; Becker, Carola; Scholtz, Gerhard (Frontiers in Psychology, 2018)
To recognize a familiar object, incoming perceptual information is matched against object representations in memory. Mounting evidence suggests that these representations are not stable, but adapt flexibly to recently encountered perceptual information. This is evident in the form of aftereffects, where prolonged exposure to one object (adaptor) influences perception of the next one (test stimulus). So far, adaptation aftereffects have been mainly shown for human faces and simple geometric shapes, and it has been concluded that face aftereffects partially derive from shape adaptation. However, it is largely unknown whether adaptation aftereffects generalize to other categories of complex, naturalistic biological objects, and if so, whether these effects can be explained by shape adaptation. To answer these questions, we conducted three experiments in which images of crabs and lobsters were presented in two versions: as complex, naturalistic images or reduced to their simplified geometric shapes. In Experiment 1, we found robust adaptation aftereffects for the complex versions of the images, indicating that adaptation aftereffects generalize to animate objects other than faces. Experiment 2 showed adaptation aftereffects for the simplified stimuli, replicating previous findings on geometric shapes. Experiment 3 demonstrated that adaptation to the simplified animal shapes results in aftereffects on the complex naturalistic stimuli. Comparisons between experiments revealed that aftereffects were largest in the first experiment, in which complex stimuli served as adaptor and test stimuli. Together, these experiments show that the magnitude of adaptation aftereffects depends on the complexity of the adaptor, but not on that of the test stimuli, and that shape adaptation plays a role in – but cannot entirely account for – the object aftereffects.